OPTIMALISASI KETERSEDIAAN SARANA DAN PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI RA EL BAHIJI SENGGIGI KECAMATAN BATU LAYAR - Azzahra, Fauzila; Kadir Jaelani, Abdul; Nada Buahana, Baiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aim to analyze the availability, management, and optimization of facilities and infrastructure to improve the quality of learning at RA EL Bahiji Senggigi Batu Layar District. This study used a qualitative approach with a descriptive approach. The research subjects consisted of the principal and teachers, while data collaction techniques were conducted therough interviews, observation, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the availability of facilities and infrastructure at RA EL Bahiji Senggigi is still limited and does not fully meet standards, particularly for education play equipment (APE), supporting spaces, and other learning facilities. Facilities and infrastructure management has been implemented through planning, utilization, and maintenance, although challenges remain in procurement and development facilities, such as teacher creativity in utilizing local and recycled materials as learning media, multifunctional use of facilities, and dhe community. These optimization efforts have had a positive impact on the quality of learning, as demonstrated by increased student activity, participation, and involvement in learning activities. Thus, despite limitations, optimally managed and utilized facilities and infrastructure can support more effective, creative, and meaningful learning for early childhood.